2002
DOI: 10.1073/pnas.072495599
|View full text |Cite
|
Sign up to set email alerts
|

MYC overexpression imposes a nonimmunogenic phenotype on Epstein–Barr virus-infected B cells

Abstract: Lymphoblastoid cell lines, generated by immortalization of normal B cells by Epstein-Barr virus (EBV)in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
58
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 48 publications
(54 reference statements)
4
58
0
1
Order By: Relevance
“…In all, 34 Myc-repressed genes were represented by this category, and 18 of them were up-regulated >4-fold upon Myc inactivation (Table 1). This was consistent with the observation that Myc overexpression renders B cells nonimmunogenic (26).…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…In all, 34 Myc-repressed genes were represented by this category, and 18 of them were up-regulated >4-fold upon Myc inactivation (Table 1). This was consistent with the observation that Myc overexpression renders B cells nonimmunogenic (26).…”
Section: Resultssupporting
confidence: 80%
“…Furthermore, future immunotherapies could use neutralizing antibodies against additional Myc-repressed B-cell differentiation markers identified by us (Mb1, lymphotoxin B, etc.) and by others (24)(25)(26). Such antibodies might be particularly effective in eliminating neoplastic cells that have survived anti-Myc therapies.…”
Section: Discussionmentioning
confidence: 99%
“…41 This nonimmunogenic phenotype is imposed by MYC expression, as it was shown in a conditional model that MYC inactivation results in upregulation of accessory molecules and antigen presentation. 42 However, the mechanism of this MYC-induced repression of immunogenicity was not clear. Our results demonstrate that IKK2/NF-B is controlling expression of several of these such as LFA-1, LFA-3, ICAM-1, TAP1, HLA-I, and HLA-2 (supplemental Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of in vitro EBV-transformed cell lines that recapitulate the BL cell phenotype through regulated expression of EBNA2/LMP-1 and c-Myc have shown that overexpression of c-Myc in the absence of LMP-1 is directly responsible for the altered immunogenicity of BL cells (Frisan et al, 1996(Frisan et al, , 1998Staege et al, 2002), which also correlates with alterations of ubiquitindependent proteolysis (Gavioli et al, 2001). BL cells were shown to be resistant to treatment with doses of proteasome inhibitors that are readily toxic for normal lymphoblasts.…”
Section: The Rescue Program: Lmp-2a and The Capture Of Cellular Ubiqumentioning
confidence: 99%